Patterns of mobility and its impact on retention in care among people living with HIV in the Manhiça District, Mozambique. - Edson L Bernardo; Tacilta Nhampossa; Kate Clouse; James G Carlucci; Sheila Fernández-Luis; Laura Fuente-Soro; Ariel Nhacolo; Mohsin Sidat; Denise Naniche; Troy D Moon (PLoS ONE)
Introduction Retention in HIV care is a challenge in Mozambique. Mozambique´s southern provinces have the highest mobility levels of the country. Mobility may result in poorer response to HIV care and treatment initiatives. Methods We conducted a cross-sectional survey to explore the impact of mobility on retention for HIV-positive adults on ART presenting to the clinic in December 2017 and January 2018. Survey data were linked to participant clinical records from the HIV care and treatment program. This study took place in Manhiça District, southern Mozambique. We enrolled self-identified migrants (moved outside of Manhiça District ≤12 months prior to survey) and non-migrants, matched by age and sex. Results 390 HIV-positive adults were included. We found frequent movement: 45% of migrants reported leaving the district 3-5 times over the past 12 months, usually for extended stays. South Africa was the most common destination (71%). Overall, 30% of participants had at least one delay (15-60 days) in ART pick-up and 11% were delayed >60 days, though no significant difference was seen between mobile and non-mobile cohorts. Few migrants accessed care while traveling. Conclusion Our population of mobile and non-mobile participants showed frequent lapses in ART pick-up. Mobility could be for extended time periods and HIV care frequently did not continue at the destination. Studies are needed to evaluate the impact of Mozambique´s approach of providing 3-months ART among mobile populations and barriers to care while traveling, as is better education on how and where to access care when traveling.